Associação entre espaçamento anterior e hábitos de sucção não nutritivos em nipo-brasileiros e leucodermas, na dentadura decídua - Ferreira, Evandro Eloy Marcone (2008)
The aims of this study were to evaluate the prevalence of anterior interdental spacing characteristics in the deciduous dentition, in Japanese-Brazilians and white Brazilians, as well as to test the association between the occlusal traits and the non-nutritive sucking habits. Two samples of both sexes, aged 2 to 6 years, were selected: 405 Japanese-Brazilians from 36 public and private schools in the State of São Paulo and 510 white children enrolled at 11 public institutions in the eastern region of São Paulo – SP. The investigation on non-nutritive sucking habits was conducted by means of a questionnaire applied to the parents/guardians. The occlusal characteristics were researched on clinical forms previously collected. Features related to the interdental spacing in the maxillary and mandibular arches were assigned to four categories: generalized spacing, only primate spaces, no spacing and crowding. The overjet was also evaluated in order to analyze a possible association between increased overjet, history of non-nutritive sucking habits and anterior spacing in the maxillary arch. Data were submitted to analytical and descriptive statistics. The occlusal characteristics were compared according to the age group and sex, in each ethnic group, using the Chi-Square test (α = 0.05). Logistic regression analysis was used to test the effect of the factors relative to the age group, sex and ethnic group on the prevalence of anterior spacing characteristics. In addition, a logistic regression model was adjusted to analyze the association between the presence of generalized anterior spacing or only primate spaces in the maxillary arch, non-nutritive sucking habits and increased overjet. In Japanese-Brazilians, generalized spacing was the most prevalent feature in the maxillary (46.2%) and mandibular (53.3%) arches. The frequency of primate spaces was higher in the maxillary arch (28.2% versus 15.3%). Concerning the characteristics related to the absence of spaces (21.7% - 26.4%) and crowding (4% - 4.9%), the variation between percentages in the maxillary and mandibular arches was relatively small. In white children, the frequencies of the characteristics related to the absence of spaces and presence of primate spaces demonstrated a distribution pattern similar to that observed in Japanese-Brazilians. Generalized spacing was diagnosed in approximately 50% of the maxillary and mandibular arches. However, the prevalence of crowding was 3 times higher in the mandibular arch (12.8% versus 3.9%). White children showed 2.8 more chances of developing mandibular crowding in comparison with Japanese-Brazilians (p = 0.000). There was no association between the prevalence of anterior spacing features and history of non-nutritive sucking habits.